MONETARY POLICY SHOCK ON INFLATION, OUTPUT, AND EXCHANGE RATE - Arintoko, Arintoko (TRIKONOMIKA, 2022)
This study aims to estimate the impact of monetary policy shocks on inflation, output, and exchange rates during the inflation-targeting period. The data analyzed are quarterly data covering the period 2005Q3 - 2020Q1. The analysis tool used is the Vector Error Correction model with the cointegration relationships between variables. The results show that there are variations in the impact of the monetary policy shock on the response of the variables in the model. Monetary policy shocks can explain the forecast error variance of policy interest rates, inflation, exchange rates, and output, respectively, with the largest to the smallest contribution. The characteristics of shocks are unexpected and unpredictable, resulting in variability and volatility of the variable responses. Therefore, reducing the impact of the monetary policy shock can improve the effectiveness of the monetary policy. Improving the effectiveness of monetary policy can be done with the support of the central bank's credibility.